2004
DOI: 10.1080/10640260490490438
|View full text |Cite
|
Sign up to set email alerts
|

Readiness to Change Dietary Restriction Predicts Outcomes in the Eating Disorders

Abstract: This study examined the relationship between readiness and motivation to change eating disorder symptoms and clinical outcomes during and following intensive residential eating disorder treatment. Sixty-four women completed the Readiness and Motivation Interview (RMI) at baseline, and a subset of participants were reassessed at post-treatment (n=45) and at 6 month follow-up (n=38). The RMI provides readiness scores for each of four symptom domains: restriction, cognitive, bingeing, and compensatory strategies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 24 publications
2
95
0
3
Order By: Relevance
“…22,34,78 Readiness for change has been examined as a predictor of rehospitalization and other individual outcomes at 6-month and 9-month follow-up. 2,3,18 While this study was carried out on a sample that had private health insurance, mental health benefits can differ substantially between plans. An indi-FIGURE 1 Kaplan-Meier (one-minus survival) curve indicating probability of favorable short-term outcome at discharge by level of readiness for change.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22,34,78 Readiness for change has been examined as a predictor of rehospitalization and other individual outcomes at 6-month and 9-month follow-up. 2,3,18 While this study was carried out on a sample that had private health insurance, mental health benefits can differ substantially between plans. An indi-FIGURE 1 Kaplan-Meier (one-minus survival) curve indicating probability of favorable short-term outcome at discharge by level of readiness for change.…”
Section: Resultsmentioning
confidence: 99%
“…1 Contemporary empirical and theoretical work has continued to highlight the low level of motivation to recover associated with AN. [2][3][4][5][6] The motivational deficiency has been partly attributed to the ego-syntonic quality of the illness as well as the patient's lack of understanding and concern regarding the seriousness of the disease. 7,8 The disease itself may serve a functional purpose for some by providing identity and a sense of selfworth despite the danger to health.…”
Section: Introductionmentioning
confidence: 99%
“…6 As individuals with AN are often characterized by marked ambivalence about changing their eating and weight, 7,8 recent research has been interested in the role that readiness to recover plays in treatment completion. Readiness to change dietary restriction has been shown to be associated with a better outcome in an intensive inpatient AN treatment program, 9 and in another study those who dropped out of treatment were found to have higher precontemplation scores (according to the Stages of Change model) at admission than those who completed intensive treatment. 7 Motivation to change eating disorder behaviors has also been shown to predict the amount of weight gained during the first 4 weeks of intensive treatment.…”
Section: Introductionmentioning
confidence: 98%
“…In fact, if it were directly assessed, individuals with AN may not endorse the ''refusal'' criterion-or related cognitive criteria B or C-for a range of reasons (for a review of relevant literature on denial in AN, see Vandereycken, 2006a,b;Vitousek et al, 1991). 46,48,49 Some patients may recognize their symptoms yet choose either not to disclose or to conceal them due to an investment in maintaining their symptoms, 38,40,41 perceived stigma attached to AN, [51][52][53][54] or their concerns about social desirability. Alternatively, other individuals may not recognize or acknowledge the symptoms because of limited insight, developmental capacity, or cognitive impairment related to their nutritional compromise.…”
Section: Patient Capacity And/or Willingness To Endorse Symptoms Are mentioning
confidence: 99%